Technique for Grafting Preexisting Bone Tunnels During the First Stage of Revision Anterior Cruciate Ligament Reconstruction - Richard Ma, M.D.; Samuel D. Hawkins, B.S.; Gregory D. Caplinger, F.N.P.; Joseph Temperato, D.O. (Arthroscopy Techniques)
The incidence of revision anterior cruciate ligament reconstruction is increasing. Anticipated convergence of malpositioned tunnels, significant graft tunnel widening, and bone loss are all indications for performing a 2-staged revision reconstruction. The goal of this Technical Note is to describe a simple bone-grafting technique for placing allograft bone matrix into femoral and tibial bone tunnels during the first stage of a 2-stage revision anterior cruciate ligament reconstruction.